UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI STRATEGI PAIKEM SISWA KELAS V SD NEGERI 241/VI MUARA DELANG I - Tugi Hari Giri Prapti; Muhammad Jainuri; Sugeng Riyadi (Hiradika | Hira Institute, 2025)
This inquiry was prompted by the low arithmetic learning results of course V students at SD Negeri 241/VI Muara Delang I, which was caused by students' lack of motivation. The point of the investigation is to enhance student learning outcomes by utilizing the PAIKEM procedure. The strategy used in this investigation is P,Tas demonstrated byhe Kemmis McTaggartion, which is actualized threen 3 cycles. The subjects of this inquiry were 25 students in lesson V of SD Negeri 241/VI Muara Delang I for the 2024/2025 academic year. Information collection strategies utilized tests, perception, and documentation. The criteria for victory in this investigation are that the student's score reaches the KKM, specifically ≥ 75, and students have completed learning ≥ 75% of the overall number of students. The use of learning utilizing the PAIKEM technique appears to increase student learning activities. Amid learning, students looked eager. This can be seen from the rate of understudy learning outcomes in cycle I (63.2%), cycle II (70.8%),() 82.8%. An increase in student learning outcomes also accompanies the increment in the rate of student learning exercises. This is evident from the classical understudy learning completion rates of 56% for cycle I, 76% forII, and for cycle IIId cycle III 84%. Based on the inquiry, it can be concluded that the application of the PAIKEM methodology can increase action and learning results of lesson V students at SD Negeri 241/VI Muara Delang I for the 2024/2025 academic year.